2020
DOI: 10.3390/ijms21010303
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Levels of Cerebrospinal Fluid/Plasma Aβ40 as an Early Biomarker for Cerebral Amyloid Angiopathy in RTg-DI Rats

Abstract: The accumulation of fibrillar amyloid β-protein (Aβ) in blood vessels of the brain, the condition known as cerebral amyloid angiopathy (CAA), is a common small vessel disease that promotes cognitive impairment and is strongly associated with Alzheimer’s disease. Presently, the clinical diagnosis of this condition relies on neuroimaging markers largely associated with cerebral macro/microbleeds. However, these are markers of late-stage disease detected after extensive cerebral vascular amyloid accumulation has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
4
9
0
Order By: Relevance
“…Consistent with these previous findings, thalamic hemosiderin deposits in the present cohort are shown in Figure S3a, c. The thalamic region of rTg-DI rats also exclusively exhibit numerous calcified, occluded microvessels and capillaries (Davis et al, 2018;Lee et al, 2020;Zhu, Hatfield, et al, 2020). Figure S3b, d show that these thalamic-calcified occluded vessels are similarly observed in the present cohort of rTg-DI rats.…”
Section: Distinct Brain Regional Pathologies Associated With Microvascular Amyloid Accumulation In Rtg-di Ratssupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with these previous findings, thalamic hemosiderin deposits in the present cohort are shown in Figure S3a, c. The thalamic region of rTg-DI rats also exclusively exhibit numerous calcified, occluded microvessels and capillaries (Davis et al, 2018;Lee et al, 2020;Zhu, Hatfield, et al, 2020). Figure S3b, d show that these thalamic-calcified occluded vessels are similarly observed in the present cohort of rTg-DI rats.…”
Section: Distinct Brain Regional Pathologies Associated With Microvascular Amyloid Accumulation In Rtg-di Ratssupporting
confidence: 91%
“…Data points show the results from each rat and the group mean ± SD of n = 6 rTg-DI rats all three brain regions the presence of thrombotic events is largely restricted to the thalamic region of rTg-DI rats (Davis et al, 2018;Lee et al, 2020;Zhu, Hatfield, et al, 2020;. For example, at 12 M, microbleeds are prominently observed bilaterally in the thalamic region based on magnetic resonance imaging and histological staining for hemosiderin (Davis et al, 2018;Lee et al, 2020;Zhu, Hatfield, et al, 2020;. Consistent with these previous findings, thalamic hemosiderin deposits in the present cohort are shown in Figure S3a, c.…”
Section: Distinct Brain Regional Pathologies Associated With Microvascular Amyloid Accumulation In Rtg-di Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate potentially different subtypes of microglia in rTg-DI rats, we performed double immunolabeling for Iba-1, a common resident microglial marker, and OX6 MHCII a marker that has been used to identify activated macrophagic microglia [22,23]. In 3 and 12-month wildtype rats, the small number of microglia were labeled exclusively with Iba-1 and exhibited their resting state morphology (Additional Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that rTg-DI rats have the potential to be a useful preclinical platform to study the pathogenesis of CAA type-1, to identify biomarkers for disease and to test therapeutic interventions. Indeed, we recently showed that decreasing levels of Aβ40 peptide in cerebrospinal fluid correlated with the progression of CAA in this model [22]. To better understand the utility of rTg-DI rats as a valid preclinical model, here we investigated the temporal development of several perivascular pathologies that are commonly observed with human CAA type-1.…”
Section: Discussionmentioning
confidence: 99%